The Financial Ripple Effect: Evaluating the Impact of Corporate Downsizing in Meta - Tatengkeng, Aaron Kevin Sammy; Damayanti, Sylviana Maya; Prirayani, Jagat (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the financial ramifications of corporate downsizing on Meta Platforms Inc., focusing on the timeframe from 2018 to 2025, which includes the company’s rapid growth and the ensuing "Year of Efficiency" layoffs commencing in late 2022. The study uses a quantitative approach, looking at changes in key financial and operational factors before and after the downsizing intervention. It does this by using Interrupted Time Series Analysis (ITSA) and multiple regression models on quarterly data. There is a lot going on with this "ripple effect." On the one hand, cutting back on staff and costs helped profits and efficiency a lot in the short run. Some numbers, like Return on Assets (ROA) and Operating Margin (OPM), went up after the company was slashed. Operating Income per Employee (OIPE) also went up. This means that employees made more money, mostly because costs were cut. On the other hand, the plan made it harder to get work done. Sales per Employee (SPE) steadily went down, which shows that fewer workers hurt production and may have hurt employee happiness. Also, cutting back on staff did not have a big effect on Return on Equity (ROE) or the Operating Cash Flow to Assets ratio (OCF). This means that laying off workers did not instantly increase short-term liquidity or returns for shareholders. Even when internal variables like R&D intensity and leverage and external macroeconomic factors like GDP growth and inflation were considered, these results stayed the same.